2014
DOI: 10.3109/00952990.2014.918623
|View full text |Cite
|
Sign up to set email alerts
|

Drinking games and contextual factors of 21st birthday drinking

Abstract: Together, these results suggest that drinking games are part of a larger context of risk contributing to extreme drinking on 21st birthdays. Furthermore, these results will help to facilitate interventions that are more individually tailored to target specific contextual risks, behaviors, and events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…More specifically, students reported 46% more consequences on days that involved pregaming. This is in line with a growing literature that highlights risk that is associated with specific drinking practices (e.g., Borsari, 2004; LaBrie & Pedersen, 2008; Merlo, Ahmedani, Barondess, Bohnert, & Gold, 2011; Merrill et al, 2013; Neighbors et al, 2014; Neighbors, Spieker, Oster-Aaland, Lewis, & Bergstrom, 2005). We also examined whether gender predicted pregaming behaviors and found that gender was not associated with pregaming or alcohol consequences.…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, students reported 46% more consequences on days that involved pregaming. This is in line with a growing literature that highlights risk that is associated with specific drinking practices (e.g., Borsari, 2004; LaBrie & Pedersen, 2008; Merlo, Ahmedani, Barondess, Bohnert, & Gold, 2011; Merrill et al, 2013; Neighbors et al, 2014; Neighbors, Spieker, Oster-Aaland, Lewis, & Bergstrom, 2005). We also examined whether gender predicted pregaming behaviors and found that gender was not associated with pregaming or alcohol consequences.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, this Special Issue includes papers that use event-specific designs to investigate contextual factors associated with drinking game behaviors. Clapp et al's study (17) is the first to examine drinking games in the context of a real party, and Neighbors et al's study (18) assesses drinking games that take place during 21st birthday celebrations. Research investigating drinking games behavior in the context of 21st birthday celebrations is particularly important given that students are at increased risk for heavy alcohol consumption on this occasion.…”
Section: Introductionmentioning
confidence: 99%
“…DGs are social drinking activities designed to promote intoxication, have rules specifying when and how much players drink, and involve doing some kind of cognitive and/or motor gaming tasks (Zamboanga et al, 2013a). Compared to other high-risk drinking behaviors, like prepartying (i.e., drinking before going out to a social event or gathering; Borsari et al, 2007) and 21 st birthday celebrations (Neighbors et al, 2014), DGs are a unique high-risk activity because they are comprised of rules expressly designed to encourage drunkenness (Zamboanga & Tomaso, 2014). Participants may in turn use these rules to target specific players for their increased intoxication (Borsari, 2004; Zamboanga et al, 2015).…”
mentioning
confidence: 99%